Association Between Lifelong Premature Ejaculation and Polymorphism of Tryptophan Hydroxylase 2 Gene in the Han Population. Issue 2 (10th March 2020) - Fu, Xu; Zhang, Xiansheng; Jiang, Tao; Huang, Yuanyuan; Cheng, Peng; Tang, Dongdong; Gao, Jingjing; Du, JunHua
Abstract: Introduction: Premature ejaculation (PE) is widely regarded as one of the most common sexual dysfunctions in men. The neurobiogenesis of PE is complex and involves the serotoninergic (5-HT) system. Aim: In this study, we investigated whether polymorphisms in the tryptophan hydroxylase 2 (TPH2) gene were associated with lifelong PE (LPE). Methods: A total of 121 men diagnosed with LPE were recruited from our outpatient clinics and 94 healthy controls from the health examination center. Intravaginal ejaculation latency time (IELT) was measured using a stopwatch. The PE diagnostic tool (PEDT) data were collected at the same time. All subjects with LPE and healthy controls were genotyped for polymorphisms in the TPH2 gene. Allele and genotype frequencies of single-nucleotide polymorphisms (SNPs) were compared between the patients and controls. Main Outcome Measure: The main outcome measures are IELT and PEDT to diagnose LPE. The association of LPE with TPH2 gene polymorphisms in these areas was investigated. Results: The IELT, PEDT scores, and education levels in the LPE group were significantly different from those in the control group. Statistically significant differences were found in the SNPs of SNV019 and rs4290270. The frequencies of the G allele and G/A genotype of SNV019 were significantly higher in the patients with LPE than in the controls ( P = .045 and .037, respectively). The A allele and A/A genotype of rs4290270 were more frequent in the patients with LPE than in the controls ( P = .037 and .049, respectively). In the dominant model of inheritance, the SNV019 polymorphism in the patients with LPE was significantly different from that in the controls (odds ratio [95% confidence interval] = 2.936 [1.066–8.084], P = .037). In men with LPE, there was no statistically significant association between genotype and median IELT. Conclusion: The SNPs SNV019 and rs4290270 of the TPH2 gene seemed to be associated with LPE in the Han population. Men with the A allele of SNV019 or the T allele of rs4290270 may be less likely to suffer from LPE.